Patients' perceptions of recovery following a 6-week exercise intervention for the treatment of patellofemoral pain: A mixed methods study - Dominique C. Leibbrandt; Quinette A. Louw (AOSIS, 2019)
Background: Patellofemoral pain (PFP) is a common and complex condition. The diagnosis and causal mechanisms are not well understood and therefore the long-term prognosis tends to be poor. Exercise is currently the only evidence-based treatment strategy suggested to improve pain and function in the long term. However, no qualitative studies have been conducted to establish patients' perceptions of recovery in the long term following an exercise intervention. Objectives: To measure self-reported recovery on a 7-point Likert scale in 31 participants with PFP 6 months after a 6-week physiotherapy intervention. To explore the subjective accounts of patients who received a physiotherapy intervention for PFP, regarding their expectations and perceptions of recovery. Method: Semi-structured exit interviews were conducted electronically 6 months after intervention to ascertain the patients' perspectives on whether expectations of treatment were met, and factors that influenced their recovery experience. Results: Quantitative analysis of self-reported recovery on a 7-point Likert scale showed that 48.4% of participants felt that they were 'recovered'. Qualitative analysis showed three main categories: expectations of treatment, perceptions of recovery and changes in functional abilities. Conclusion: Clinicians should address patients' expectations of treatment and include the patients in decision-making regarding their treatment. Long-term follow-up is essential to ensure that treatment effects have been maintained, and this should include information about patients' self-reported recovery. Clinical implications: This study suggests that patients' expectations of treatment and perceptions of recovery from PFP may influence prognosis. Clinicians need to collaborate with patients and involve them in decision-making to achieve their goals. An individualised treatment approach is essential to adequately address patients' experiences, priorities and beliefs.